Strategi Pemasaran Kedai R&F Coffee di Kelurahan Sinindian Kecamatan Kotamobagu Timur Kota Kotamobagu - Olii, Silvi Suripto; Mandei, Juliana Ruth; Jocom, Sherly Gladys (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2026)
This study aims to identify the marketing strategies implemented by Kedai R&F Coffee in Sinindian Village, East Kotamobagu District, Kotamobagu City. This study was conducted from May to July 2025. Primary data were obtained through observation, interviews, and questionnaires. Respondents interviewed were the owner of Kedai R&F Coffee and consumers using questionnaires. Secondary data were obtained from company documents, and literature or references related to the study. With a total of 60 respondents. The sampling technique used was accidental sampling. Data analysis used in this study was descriptive analysis. The results showed that there were 7 aspects of the marketing mix strategy implemented by Kedai R&F Coffee, namely (Product, Price, Promotion, Place, People, Process and Physical Evidence). Consumer assessment of the 7 aspects of the marketing mix strategy implemented by Kedai R&F Coffee, namely on the aspects of Product, Price, Place, People, Process and Physical Evidence, was considered good, and for the Promotion aspect it was considered quite good. Consumer assessment of the 7 aspects of the marketing mix obtained an overall score of 2,877 which was categorized as good.